Kualitas Organoleptik Tempe Dari Kacang Tanah, Kacang Hijau, dan Kacang Komak - Riana Azizah; Nining Purwati (Politeknik Negeri Ketapang, 2025)
Organoleptic quality evaluation of tempeh made from groundnut, mung bean and komak bean was conducted to compare it with soybean tempeh. The research process involved tempeh making methods and organoleptic testing conducted by 10 panelists via Google Form. Tempeh from peanuts received the highest rating, with 70% of the panelists liking the color and texture, and 60% giving a positive rating for the taste. Meanwhile, mung bean tempeh only received 40% positive ratings for taste and 50% for color. Tempeh from komak beans showed similar results, with 50% of panelists dissatisfied with the color and aroma. Soybean tempeh remains the highest quality benchmark. Groundnut tempeh showed better potential in consumer acceptance, while tempeh from mung bean and komak need further evaluation and improvement to attract the public to accept the different raw materials.